Corporate governance in emerging economies: A focus on sustainable development - Omar Hasan Ahmed; Hayder Mohammed Hassan; Wissam Anwar Mohammed Hassan Ali; Haider Mahmood Jawad; Khdier Salman (Environment and Social Psychology, 2025)
Corporate sustainability is a force that is brought by corporate governance, particularly in the emerging economies whose regulatory systems are still evolving. The article will examine the relationship between the governance mechanisms such as, Board independence, transparency and stakeholder engagement and the sustainability outcomes that are the environmental and social performance metrics. The study relies on statistical frameworks to explain the governance structures that promote carbon emissions and community investments using a sample of 150 publicly listed companies in Southeast Asia, Sub-Saharan Africa, and Latin America. The findings have indicated that more board independence and transparency in organizations lead to reduced carbon emission, and that those organizations that seek more stakeholder involvement commit more resources to social activities. Sectoral and regional disparities provide an indication of industries with the highest regulatory supervision, such as technology and renewables to be more successful in the outcomes of sustainability generated by governance than traditional sectors, such as manufacturing or agriculture. The results provide a picture that to ensure the effective approach to common good issues, the governance regulations should be improved and accompanied by the obligatory sustainability reports, in addition to the stakeholder involvement in the corporate sphere. It also highlights the importance of having governance systems that are configured to regional and sectoral circumstances. Having these results, the paper contributes to the existing body of empirical research on the governance-sustainability nexus by providing fresh concepts on corporate governance and sustainability in the emerging market settings. The researchers can examine how long-term effectiveness of governance reforms on corporate sustainability and the effect of macroeconomic conditions on effective governance in future.